Speech Act of Directive Utterances in Sherlock Holmes "Scarlet" - Bhinthamie, Anthien; , Drs. Maryadi M. A.; , Nur Hidayat S. Pd., M. Pd (2015)
SUMMARY Anthien Bhinthamie, A320110036. "Speech Act of Directive Utterances in Sherlock Holmes "Scarlet"". Muhammadiyah University of Surakarta. Research Paper. 2015. The objective of the research is to describe forms and intention of directive utterance. The data source is Sherlock Holmes: A Study in Scarlet novel. The object to be analyzed are speech act of directive utterances in Sherlock Holmes: A Study in Scarlet novel. This research is descriptive qualitative research. The writer uses documentation as the method of collecting the data in this research. The method of documentation are reading the novel, signing the directive utterance, and gathering the data. The result of the research shows that: First, the writer finds three kinds of directive form, they are: declarative sentence, imperative sentence, and interrogative sentence. The imperative sentences are divided into two categories: imperative sentence ended by exclamatory mark and ended by full stop. Second, the roles of directive utterance are classified into four types: command, requesting, suggestion, and invitation. Keywords: directive utterance, pragmatic, speech act